2008
DOI: 10.1211/ijpp.16.4.0006
|View full text |Cite
|
Sign up to set email alerts
|

Development and use of the critical incident technique in evaluating causes of dispensing incidents

Abstract: Aims and objectivesThe study aimed to evaluate the causes of prevented dispensing incidents reported by hospitals using the critical incident technique developed by key-informant interviews, focus group and observation. Setting All Welsh NHS hospitals (n = 20) were invited to participate in the study. Sixteen hospitals agreed to take part; 10 hospitals reported incidents, four hospitals did not report any incidents and two hospitals withdrew from the study. Method In June 2005 three key-informant interviews an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(50 citation statements)
references
References 36 publications
(54 reference statements)
0
50
0
Order By: Relevance
“…[1] However, the UK NPSA patient safety taxonomy for unprevented and prevented patient safety incidents was only adopted by four of the reviewed UK papers undertaken after 2004. [44,47,48,72] The World Health Organization is currently developing global patient safety taxonomy. [77,78] Therefore, it is anticipated that the World Health Organization taxonomy will facilitate consistent data collection, sharing of patient safety information and the development of global solutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] However, the UK NPSA patient safety taxonomy for unprevented and prevented patient safety incidents was only adopted by four of the reviewed UK papers undertaken after 2004. [44,47,48,72] The World Health Organization is currently developing global patient safety taxonomy. [77,78] Therefore, it is anticipated that the World Health Organization taxonomy will facilitate consistent data collection, sharing of patient safety information and the development of global solutions.…”
Section: Discussionmentioning
confidence: 99%
“…[23,29] Reason's human error theory was employed in three reviewed papers to understand the aetiology of prevented dispensing incidents in UK hospital pharmacies. [40,43,48] Analysis of staff interviews [40,43] and self-completed critical incident report forms [48] revealed that prevented dispensing incidents were caused by a complex interweaving of active failures (slips, lapses and mistakes), latent conditions and errorproducing conditions. Slips were identified as selecting the wrong drug or strength of medication, lapses involved forgetting to remove inappropriate cautionary labels during label generation, and mistakes involved assumptions that products were interchangeable, doses were the same as previously recorded in patient medication record and dispensing in accordance with labels rather than prescriptions.…”
Section: Error Types In the Usmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies (one reported in two papers) used retrospective reviews of disciplinary/performance records to explore performance [38][39][40]61,62,68,71]. Three studies used retrospective analysis of error data [52,53,72], whilst seven studies used prospective data collection techniques on errors [37,42,56,69,70] or clinical interventions [50,64]. Other less common methods used included critical incident technique [52], simulation testing in hypothetical scenarios [65], review of prescription monitoring incidents [41], analysis of claims data [59], videotaping and review of pharmacist performance [46], a controlled study exploring impact of ambient sounds on errors [47], comparison of error rates at different illumination levels [44], root-cause analysis of transcription errors [57], and a literature review (Table 1) [51].…”
Section: Research Methods Usedmentioning
confidence: 99%
“…Of the identified studies, the majority were published in either the USA (n = 15) [43][44][45][46][47][54][55][56]58,59,61,[64][65][66]70], or the UK (n = 14) [37,41,42,[48][49][50]52,53,60,68,69,[71][72][73]. Two studies were conducted in Canada [38][39][40], two in Australia [62,63] and two in Europe [57,67].…”
Section: Country Of Publicationmentioning
confidence: 99%